Antibacterial effect of urushiol on E. faecalis as a root canal irrigant - Sang-Wan Kim; Dong-Hoon Shin (Korean Academy of Conservative Dentistry, 2017)
Objectives The purpose of this study was to compare the antibacterial activity of urushiol against Enterococcus faecalis (E. faecalis) to that of NaOCl. Materials and Methods The canals of thirty two single rooted human teeth were instrumented with Ni-Ti files (ProTaper Next X1, X2, X3, Dentsply). A pure culture of E. faecalis ATCC 19433 was prepared in sterile brain heart infusion (BHI) broth. The teeth were submerged in the suspension of E. faecalis and were incubated at 37℃ for 7 days to allow biofilm formation. The teeth were randomly divided into three experimental groups according to the irrigant used, and a negative control group where no irrigant was used (n = 8). Group 1 used physiologic normal saline, group 2 used 6% NaOCl, and group 3 used 10 wt% urushiol solution. After canal irrigation, each sample was collected by the sequential placement of 2 sterile paper points (ProTaper NEXT paper points, size X3, Dentsply). Ten-fold serial dilutions on each vials, and 100 µL were cultured on a BHI agar plate for 8 hours, and colony forming unit (CFU) analysis was done. The data were statistically analyzed using Kruskal-Wallis and Mann-whitney U tests. Results Saline group exhibited no difference in the CFU counts with control group, while NaOCl and urushiol groups showed significantly less CFU counts than saline and control groups (p < 0.05). Conclusions The result of this study suggests 10% urushiol and 6% NaOCl solution had powerful antibacterial activity against E. faecalis when they were used as root canal irrigants.